Occurrence and clinical correlates of SARS-CoV-2 viremia in two German patient cohorts - Katharina Grikscheit; Annemarie Berger; Holger Rabenau; Niko Kohmer; Katharina S. Appel; Margarete Scherer; Robert Bals; Sabine Blaschke; Axel Hamprecht; Sina M. Hopff; Dagmar Krefting; Patrick Meybohm; et al. (Emerging Microbes and Infections)
Viremia defined as detectable SARS-CoV-2 RNA in the blood is a potential marker of disease severity and prognosis in COVID-19 patients. Here, we determined the frequency of viremia in serum of two independent COVID-19 patient cohorts within the German National Pandemic Cohort Network (German: Nationales Pandemie Kohorten Netzwerk, NAPKON) with diagnostic RT-PCR against SARS-CoV-2. A cross-sectional cohort with 1122 COVID-19 patients (German: Sektorenuebergreifende Platform, SUEP) and 299 patients recruited in a high-resolution platform with patients at high risk to develop severe courses (German: Hochaufloesende Plattform, HAP) were tested for viremia. Our study also involved a comprehensive analysis and association of serological, diagnostic, and clinical parameters of the NAPKON medical dataset. Prevalence of viremia at the recruitment visit was 12.8% (SUEP) and 13% (HAP), respectively. Serological analysis revealed that viremic patients had lower levels of SARS-CoV-2 specific antibodies as well as lower neutralizing antibodies compared to aviremic patients. Viremia was associated with severity (<0.0001 SUEP; 0.002 HAP) and mortality of COVID-19 (both cohorts <0.0001) compared to aviremic patients. While rare, viremia was also detected in patients with mild disease (0.7%). In patients of the SUEP cohort with acute kidney disease (p = 0.0099) and hematooncological conditions (p = 0.0091), viremia was detected more frequently. Compared to the aviremic group, treatment with immunomodulating drugs as well as elevated levels of inflammatory markers in the blood was more frequent in the viremic group. In conclusion, our analysis revealed that detectable viremia correlates with hyperinflammatory conditions and higher risk for severe COVID-19 disease.